Survey of Practices by Growers in the Virginia–Carolina Region Regarding Digging and Harvesting Peanut. Issue 1 (1st November 2019) - Jordan, David L.; Hare, Andrew T.; Roberson, Gary T.; Ward, Jason; Shew, Barbara B.; Brandenburg, Rick L.; Anco, Dan; Thomas, James; Balota, Maria; Mehl, Hillary; Taylor, Sally
Abstract : Core Ideas: Harvesting peanut requires approximately twice as much time to complete as the time required for digging peanut. Fifty‐six percent of growers predicted when optimum yield would occur based on the sample provided within the recommended timeframe. Reported yield was positively correlated with the use of prohexadione calcium.